Screen acting up close : three dynamic film and TV master-classes for actors. (Clever Boy Media, 2010)
A TV director, producer, and casting director come together to provide three masterclasses for actors of all levels. Casting director Catherine Willis gives an overview of the audition process; TV director Nic Phillips highlights some basic techniques every actor has to master in front of the camera; and producer Tim Kent provides some essential advice on finding an agent and making the most out of your career.